Data hiding within color images based on MCT with x-or operations - Abduallah, Wafaa Mustafa; Rahma, Abdul Monem S.; Pathan, Al-Sakib Khan (2013)
In this paper, we present an efficient scheme of color image steganography based on Mix Column Transform (MCT) on specified blocks selected according to secret key and hide the secret message within those using logical X-OR operation. Our experiments show that the security can be increased by following this method since it uses irreducible polynomial mathematics within its operational method. The results have proven increased capacity with maintaining reasonable level of imperceptibility of the hidden data inside color images. We also present the comparisons of our approach with previous related works and show the efficiency of our method.